2013
DOI: 10.9720/kseg.2013.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Time Series of Alluvial Groundwater Levels before and after Barrage Construction on the Lower Nakdong River

Abstract: Increasing the river cross-section by barrage construction causes rises in the average river water levels and discharge rates in the rainy season. The time series patterns for groundwater levels measured at 23 riverside monitoring wells along the lower Nakdong River are compared for two cases: before and after water-filling at the Changnyeong-Haman Barrage. Monthly average groundwater levels indicate a distinct increase in groundwater levels in the upstream riverside close to the barrage. River-water level man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…As mentioned above, the backflow of saltwater was flowed into the river downstream during the summer season, which increased the EC concentration. However, the normal and low loading appeared from August 2012 due to low EC concentration because of the stabilization of the upstream river water level by the completed weirs [25]. The range of fluctuation of water level was decreased by the weirs after the barrage construction in the Nakdong River basin [26].…”
Section: Application Results Of the Developed Enhanced Monitoring Toomentioning
confidence: 99%
“…As mentioned above, the backflow of saltwater was flowed into the river downstream during the summer season, which increased the EC concentration. However, the normal and low loading appeared from August 2012 due to low EC concentration because of the stabilization of the upstream river water level by the completed weirs [25]. The range of fluctuation of water level was decreased by the weirs after the barrage construction in the Nakdong River basin [26].…”
Section: Application Results Of the Developed Enhanced Monitoring Toomentioning
confidence: 99%
“…The Quaternary alluvium has an average thickness of 1 to 33 m and is distributed predominantly along the sides of the Nakdong River and its tributaries. Kim et al [38] reported a sand layer with a thickness of 0.3 to 4 m, a gravel layer with a thickness of 1 to 10 m, and a weathered zone with a thickness of 1 to 3 m in and around the study area. On the basis of shallow hydrogeological profiles in the study area (Figure 2), the alluvial aquifer is composed of clay, sand, gravel, and weathered layers.…”
Section: Study Areamentioning
confidence: 85%
“…Thus, the influence of river‐level variations on the groundwater level decreased, and was largely controlled by precipitation. Principal component analysis also showed that the effect of the river‐level component that contributes to change in groundwater level decreases after weir construction; consequently, other factors, including groundwater pumping, become more important (Kim et al , ).…”
Section: Resultsmentioning
confidence: 99%